IMPLEMENTASI PENDEKATAN TEOLOGIS NORMATIF DALAM PLURALISME BERAGAMA DI INDONESIA - Devi, Aulia Diana; Andrean, Seka (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
This paper aims to describe the normative theological approach to religious pluralism in Indonesia. Research methods are used with the library study approach through library sources from various sources of literature on normative theological approaches in religious pluralism. Then analyzed and presented the data findings objectively. The result of this research is the implementation of normative approaches in religious pluralism in Indonesia through two elements, namely; first, uphold religious tolerance by respecting each other and respecting each other among other religions according to the practice of pancasila. second, the attitude of help in religion manifested in the form of mutual gotong royong in helping others in order to realize the welfare of each other's lives. This means that religious pluralism is an important point in people's lives in Indonesia that have different populations of different races, tribes, ethnicities, and religions.